Towards an effective modelling and development of educational games with subject-matter: A multi-domain framework - Ahmad, M. (Institute of Electrical and Electronics Engineers Inc., 2015)
Game-based learning systems or educational games have highly influenced the learning industry over the past decade. The modeling and development of an effective educational game has been a constant challenge for game developers in understanding the relationships between game play (rules and regulations), game environment, learning theories, and the subject-matter (learner's achievement to achieve the objective of subject content) embedded in the educational game. Thus, the authors have proposed a multi-domain framework to conceptualize the elements with extracted implicit relationships through a systematic literature review. These relationships are verified through qualitative interviews with eight (8) game-based learning experts to validate the relationships. This paper presents eleven (11) implicit relationships based on subject-matter domain and discusses their relevancy with game environment, learning theories, and game play by applying interpretive hermeneutic approach of qualitative study. Consequently, this paper concludes eleven (11) explicit relationships for game developers to reflect on during the modelling and conceptualizing educational games in the development process. Â© 2015 IEEE.